Potensi Streptomyces sp. Terhadap Penurunan Virulensi Bakteri Ralstonia solanacearum dalam Skala In vitro - Sa'adah, Fatimah Lailatus; Suryaminarsih, Penta; Prasetyawati, Endang Triwahyu (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2024)
The demand for chili peppers in Indonesia continues to increase, but in 2021 there was a decrease in chili production. One of the main causes is pathogen attack, especially Ralstonia solanacearum which causes bacterial wilt disease in chili plants. This study aims to evaluate the potential of Streptomyces sp. isolates BMP and TMP to reduce the virulence of R. solanacearum. The research was conducted through a series of laboratory experiments, including an inhibition test with double-layer method and virulence reduction test on Triphenyl Tetrazolium Chloride (TZC) media. The results showed that the TMP isolate was able to produce an inhibition zone of 1.5 cm2 while the BMP isolate showed no inhibition zone. In addition, this study also evaluated the virulence reduction of R. solanacearum due to the treatment of Streptomyces spp. The virulence reduction test showed that TMP isolates were able to reduce virulence by 70% while BMP isolates were able to reduce the virulence of R. solanacearum by 4%. These findings provide new insights into the development of R. solanacearum control strategies. In conclusion, isolates of Streptomyces sp. especially BMP showed potential in reducing the virulence of R. solanacearum, thus providing new hope in efforts to increase chili production sustainably.